Contamination of Fusarium spp. and mycotoxins at different ear physiological stages of maize in Argentina - Arata, Agustín Francisco; Martínez, Mauro; Pesquero, Natalia Victoria; Cristos, Diego Sebastian; Dinolfo, María Inés (Elsevier, 2024)
Maize is one of the most important crops worldwide, being affected by several fungal species under field conditions. The study of plant-pathogen interaction plays a key role because fungal diseases are responsible for reducing grain yield and quality by increasing mycotoxin production. Thus, the present work aimed to evaluate the interaction of F. graminearum and F. verticillioides and mycotoxin production under field conditions along different physiological stages. During the 2019/2020 and 2020/2021 growing seasons, twelve maize genotypes were inoculated at the flowering stage (silking). Four treatments were applied using one isolate of each species: (i) F. graminearum; (ii) F. verticillioides; (iii) a combined inoculum (F. graminearum + F. verticillioides); (iv) and control treatment. Fungal diversity, disease evaluation, and mycotoxin contamination were evaluated at three different physiological stages: T1 (from R2 to R4), T2 (from R4 to R6), and T3 (at harvest time). A total of 15,907 Fusarium isolates were obtained. The results showed a predominance of F. verticillioides over F. graminearum in both years evaluated, reporting an increase in the occurrence of this species at late stages. Regarding mycotoxin contamination, no evidence was found supporting antagonism or synergism regarding isolates of both species used as inoculum under field conditions. The results reported in the present manuscript point out a major influence of climatic conditions on F. verticillioides predominance over F. graminearum, mainly during the late physiological stages. Furthermore, no clear relationship between mycotoxin concentration and physiological stages was established, suggesting that other grain factors, such as water activity and pH, could modulate mycotoxin production and accumulation under field conditions. //Resumen: El maíz es uno de los cultivos más importantes a nivel mundial, siendo afectado por varias especies de hongos en condiciones de campo. El estudio de la interacción planta-patógeno juega un papel clave porque las enfermedades fúngicas son responsables de Reducir el rendimiento y la calidad del grano al aumentar la producción de micotoxinas. Así, el presente trabajo tuvo como objetivo evaluar la interacción de F. graminearum y F. verticillioides y la producción de micotoxinas en condiciones de campo a lo largo diferentes etapas fisiológicas. Durante las temporadas de cultivo 2019/2020 y 2020/2021, doce genotipos de maíz fueron inoculados en la etapa de floración (sudación). Se aplicaron cuatro tratamientos utilizando un aislado de cada especie: (i) F. graminearum; (ii) F. verticillioides; (iii) un inóculo combinado (F. graminearum + F. verticillioides); (iv) y tratamiento de control. La diversidad de hongos, la evaluación de enfermedades y la contaminación por micotoxinas se evaluaron en tres diferentes etapas fisiológicas: T1 (de R2 a R4), T2 (de R4 a R6) y T3 (en el momento de la cosecha). Un total de 15.907 Se obtuvieron aislados de Fusarium. Los resultados mostraron un predominio de F. verticillioides sobre F. graminearum en ambos años evaluados, reportándose un aumento en la ocurrencia de esta especie en etapas tardías. Respecto a las micotoxinas contaminación, no se encontró evidencia que respalde el antagonismo o sinergismo respecto de los aislados de ambas especies utilizado como inóculo en condiciones de campo. Los resultados reportados en el presente manuscrito señalan una influencia importante de las condiciones climáticas en el predominio de F. verticillioides sobre F. graminearum, principalmente durante finales etapas fisiológicas. Además, no existe una relación clara entre la concentración de micotoxinas y los efectos fisiológicos. Se establecieron etapas, lo que sugiere que otros factores del grano, como la actividad del agua y el pH, podrían modular la Producción y acumulación de micotoxinas en condiciones de campo.